Improving patient and project outcomes using interorganisational innovation, collaboration and co-design - Evans, Liz (London J Prim Care (Abingdon), 2014)
Background Common mental disorders (CMDs) are a leading cause of disability. The Department of Health has launched a large-scale initiative to improve access to evidence-based psychological treatments, such as cognitive behavioural therapy (CBT), through the Improving Access to Psychological Therapy (IAPT) programme. Access to IAPT services by black and minority ethnic (BME) communities is lower than for other groups. Setting The London Borough of Ealing in west London; a diverse borough with areas of high BME population and relatively high deprivation. Aim To compare the outcomes of two linked quality improvement (QI) projects undertaken by Ealing Mental Health and Wellbeing Service (MHWBS), both with the same aim of increasing access to talking therapies for BME communities. Methods Application of QI methodologies supported by the NIHR CLAHRC for northwest London in two different settings in Ealing. One, the ‘Southall project’, was set within a wider initiative for collaborative improvements and shared learning (the Southall Initiative for Integrated Care) in an ethnically diverse area of Ealing; it was undertaken between April 2010 and September 2011. The second, ‘the Ealing project’, operated in the two other Ealing localities that did not have the advantage of a broader initiative for collaborative improvements; it was undertaken between April 2011 and September 2012. Results Comparison of the monthly referral rates of BME patients (standardised per 10 000 general practitioner (GP)-registered patients) show that the Southall project was more effective in increasing referrals from BME communities than the Ealing project. Conclusion Broad local participation and ownership in the project design of the Southall project may explain why it was more effective in achieving its aims than the Ealing project which lacked these ownership-creating mechanisms.